Study of scale effect on strength characteristic of stabilised composite with sewage sludge – Part B: Critical investigation - Amiralian, Saeid; Budihardjo, Mochamad Arief; Chegenizadeh, Amin; Nikraz, Hamid (ELSEVIER, 2015)
The preliminary study of the engineering properties of bentonite composites with and without added sludge by testing the pH, compaction, and consolidation has been discussed in part A. Further critical investigations were then performed to gain an understanding of the scale effect on soil strength characteristics and the microanalytical behaviour of soil composites. Research using two different sized direct shear boxes yielded more applicable data for applying to in situ soil. It was revealed that soil was slightly strengthened by the utilisation of sludge. Experimental data were then confirmed by further microstructural, chemical, elemental and mineralogical tests.